House Price Expectations - Geng Niu; Arthur van Soest (Institute for the Study of Labor (IZA), 2014)
Utilizing new survey data collected between 2009 and 2014, this paper analyzes American households' subjective expectations on future home values. We explore the relationship between house price expectations, local economic conditions, and households' individual characteristics. We examine the heterogeneity in expectations based on panel data models. In particular, we estimate the individual- and time-specific subjective probability distributions for five-year-ahead home values. House price expectations vary significantly over time, and are positively related to past housing returns and perceived economic conditions. There is large variation in both the central tendency and the uncertainty of expectations on future home values across individuals, which is associated with several socio-economic and demographic factors. Comparing expectations and realizations shows that households only partially anticipated the large downward changes in home values in the time period 2009-2011.
Keywords: D84; R31; E31; 330; subjective expectations; house price; survey data